Purification of alkaline phosphatase and measurement of some antioxidants in the serum of patients with high blood cholesterol - Nuha Ali Hadi al-Samarrai; Mohammed J.M.Hrwsh; Miami hussin ali; Reem Ibrahim Mahdi; Mays subhi wasmi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study included the purification of the alkaline phosphatase and the estimation of the level of antioxidants in the serum of people .Those with high cholesterol. 33 blood samples were collected from people with high cholesterol in the blood of both sexes, with ages ranging between (60-42 years), and 20 blood samples were collected from people with normal cholesterol levels for both sexes.The alkaline phosphatase was also purified, as the degree of purification of the enzyme in the purification stage reached 2.7 times, with an enzymatic yield of 42.2%, and then using the gel filtration chromatography method using Sephadex G100 gel, as a single peak was obtained for the purified enzyme as ,with a degree of purification that reached 3.8 times and an enzymatic yield of 22%. High cholesterol leads to cardiovascular disease. The results a Significat increase in activity of ALP ,Cholestrol ,Lipoprotiens, catales,uric acid.The decrease total protie and Glutathion